2004
DOI: 10.1023/b:verc.0000040243.30199.1f
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Dexamethasone after Intravenous Administration in Camels: Effect of Dose

Abstract: The pharmacokinetics and pharmacodynamics of dexamethasone were evaluated in healthy camels after single intravenous bolus doses of 0.05, 0.1 and 0.2 mg/kg body weight. Dexamethasone showed dose-independent pharmacokinetics. The pharmacokinetic parameters of the two-compartment pharmacokinetic model for the lowest intravenous dose (mean+/-SD) were as follows: terminal elimination half-life 8.17 +/- 1.79 h; total body clearance 100.7 +/- 52.1 (ml/h)/kg; volume of distribution at steady state 0.95 +/- 0.23 L/kg;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Consequently, this might suggest that dexamethasone‐induced hydrocortisone suppression also is a graded and not a dichotomous response. Furthermore, a plasma dexamethasone concentration–hydrocortisone response relationship has also been shown in humans and in camels (Mager et al ., ; Al Katheeri et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, this might suggest that dexamethasone‐induced hydrocortisone suppression also is a graded and not a dichotomous response. Furthermore, a plasma dexamethasone concentration–hydrocortisone response relationship has also been shown in humans and in camels (Mager et al ., ; Al Katheeri et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, marked increase in glucose levels was observed, which is one of the adverse effect attributed to dexamethasone. The previous study has reported that treatment with dexamethasone increases glucose level by promoting hepatic gluconeogenesis and inhibit its peripheral utilization [26]. The waste product of protein metabolism, urea is eliminated through renal route.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…However, clearance of a particular drug may vary considerably among animals, for example meloxicam clearance in camels and horses is 2 and 91 mL·h/kg, respectively; hence, extrapolating dose regimens from one species to the other is not appropriate. This practice, however, was because of the lack of integrated PK/PD modeling of drugs in camels (Al Katheeri et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%